Later works : - Wright, Richard (The Library of America, 1991)
Black Boy (American Hunger) serves as a the real life basis for the novels in the first volume of this collection. It relates Wright's experiences growing up in the south and gradually moving north, ultimately to Chicago. It's fascinating and completely believable and really points out the absurdities of racism and Jim Crow-ism, as well as the coldness of the northerners. The Outsider is a departure from much of Wright's other work. While about a black character, it is essentially a musing on the intellectual and physical power one has, and their ability to wield it undetected, as long as they fit into another's stereotypes